PENGEMBANGAN GERAKAN LITERASI BERBASISKAN EMPAT KECAKAPAN BAHASA DI SMPN 220 JAKARTA DAN SMPN 274 JAKARTA - Mutiara, Rika (Universitas Esa Unggul, 2019)
AbstractDeveloping studentsÃ¢â‚¬â„¢ literacy is one of the programs conducted at SMPN 220 Jakarta and SMPN 274 Jakarta. This program focused on language literacy. However, reading is the only focus of this program. The follow-up activity is summarizing the reading texts. The schools realize that there are many other activities that can be done in developing language literacy. However, they did not have enough time and capacity to develop such program. This community service program aims at developing literacy program in which all language skills, namely listening, speaking, reading, and writing are included. It began with observation and discussion with the teachers. Next, the program was developed based on schoolsÃ¢â‚¬â„¢ needs. In applying the program, the students of Faculty of Education and Teacher Training played roles as the facilitators in the class. Through this program, all language skills were applied. It also sharpened studentsÃ¢â‚¬â„¢ cognitive and affective aspects. Cognitive aspects include think critically, find information, and give opinions. Affective aspects such as being sensitive to others became one of the concerns. This program also shows to the students that literacy program is not a boring activity due to its various activities. Some activities such as role playing entertained the students. It was found that the students have positive point of view on the literacy program conducted through this community service.Ã‚Â Keywords: literacy, language skills, readingÃ‚Â AbstrakGerakan Literasi Sekolah di SMPN 220 Jakarta dan SMPN 274 Jakarta hanya berfokus pada kegiatan membaca.Kegiatan membaca biasanya diikuti oleh kegiatan meringkas baik secara lisan maupun tulisan. Walaupun sekolah menyadari bahwa literasi dapat dikembangkan melalui kegiatan lain, sekolah masih belum mengembangkan program yang seperti itu. Oleh karena itu, kegiatan pengabdian masyarakat ini bertujuan untuk mengembangkan gerakan literasi sekolah sehingga keterampilan bahasa yang lain yaitu mendengarkan, berbicara, membaca, dan menulis juga berkembang. Kegiatan ini diawali dengan observasi dan diskusi dengan pihak sekolah.Selanjutnya, program gerakan literasi dikembangkan.Pelaksanaan pengembangan gerakan literasi tersebut dilakukan oleh mahasiswa yang didampingi oleh dosen.Melalui kegiatan ini, sekolah mengalami pelaksanan gerakan literasi yang mencakup seluruh aspek bahasa.Kegiatan tersebut mengasah kompetensi siswa di ranah kognitif dan afektif siswa.Aspekkognitif mencakup berpikir kritis, menggali informasi, dan mengemukakan pemikiran.Aspek afektif seperti kepekaan sosial dan emosi ditingkatkan.Kegiatan literasi juga memberi gambaran kepada siswa bahwa literasi tidak membosankan karena kegiatan yang dilakukan beragam.Kegiatan tertentu seperti bermain peran bersifat memberi hiburan bagi siswa.Kegiatan literasi yang diselenggarakan selama pengabdian masyarakat ini dipandang sebagai sesuatu yang positif.Ã‚Â Kata kunci: literasi, kecakapan bahasa, membaca